AI-enhanced digital therapeutics for cognitive impairment: integrating mobile applications, virtual reality, and wearable devices - Dian Jiao (Discover Artificial Intelligence)
Abstract Cognitive decline affects over 50 million people globally, with prevalence expected to triple by 2050. AI-driven digital therapeutics—encompassing mobile applications, virtual reality, and wearable devices—offer transformative opportunities for cognitive rehabilitation by leveraging adaptive algorithms and real-time feedback to deliver personalized interventions. This review systematically examines these technologies, highlighting their unique strengths in enhancing cognitive functions while acknowledging their limitations: mobile applications face retention challenges despite demonstrated effectiveness; virtual reality provides immersive environments that enhance motivation and ecological validity yet struggles with usability issues; and wearable devices offer continuous monitoring but encounter data integration and compliance difficulties. The integration of artificial intelligence enables dynamic personalization, predictive analytics, and multi-modal data fusion, creating unified therapeutic ecosystems that enhance outcomes despite persistent challenges related to data security, ethics, and algorithmic transparency. By addressing these limitations and leveraging AI's adaptive potential, digital therapeutics can revolutionize cognitive rehabilitation, improving health outcomes and quality of life for individuals with cognitive impairments worldwide.